Solving a multicoloring problem with overlaps using integer programming - Méndez Díaz, Isabel (2010)
This paper presents a new generalization of the graph multicoloring problem. We propose a Branch-and-Cut algorithm based on a new integer programming formulation. The cuts used are valid inequalities that we could identify to the polytope associated with the model. The Branch-and-Cut system includes separation heuristics for the valid inequalities, specific initial and primal heuristics, branching and pruning rules. We report on computational experience with random instances.